Integration of assisted partner services within Kenya's national HIV testing services program: A qualitative study - Beatrice M. Wamuti; Mercy Owour; Chris Obong'o; Wenjia Liu; Edward Kariithi; Harison Lagat; George Otieno; Monisha Sharma; David A. Katz; Sarah Masyuko; Carey Farquhar; Bryan J. Weiner (Public Library of Science (PLoS), 2023)
Assisted partner service (aPS) augments HIV case-finding among sex partners to individuals newly diagnosed with HIV. In 2016, aPS was incorporated into the national HIV testing services (HTS) program in Kenya. We evaluated the extent of, barriers to, and facilitators of aPS integration into HTS. We conducted semi-structured in-depth interviews (IDIs) with 32 stakeholders selected using purposive sampling at national, county, facility, and community levels. IDIs were conducted at two timepoints, at baseline from August-September 2018 in Kisumu and January-June 2019 in Homa Bay, and at follow-up from May-August 2020 to understand changes in aPS integration over time. We defined integration as the creation of linkages between the new intervention (aPS) and the existing HTS program. Data were analyzed using thematic content analysis. We found varying degrees of aPS integration, highest in procurement/logistics and lowest in HTS provider recruitment/training. At baseline, aPS integration was low and activities were at an introductory phase. At follow-up, aPS was integrated in almost the entire HTS program with the exception of low community awareness, which was noted at both baseline and follow-up. There was increasing routinization with establishment of clear aPS cycles, e.g., quarterly data review meetings, annual budget cycles and work-plans. Major barriers included limited government funding, staff constraints, and inadequate community-level sensitization, while key facilitators included increased resources for aPS, and community health volunteer (CHV) facilitated awareness of aPS. Varying degrees of aPS integration across different units of the national HTS program highlights challenges in funding, human resource, and public awareness. Policymakers will need to address these barriers to ensure optimal provision of aPS.